Positivación y protección de los derechos humanos: aproximación colombiana - Tovar, Luis Freddyur (2023)
The aim of this article is to study different ways in which the Colombian legal system protects human rights. This is done because of the emphasis given by jurists to the idea that, without legal mean s to protect human rights, such rights would become a very important moral discourse, but restricted to semantics, without any enforcement.